2017
DOI: 10.3390/jmse5040047
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Driven Overturning, Mixing and Upwelling in Shallow Water: A Nonhydrostatic Modeling Study

Abstract: Abstract:Using a nonhydrostatic numerical model, this work demonstrates that onshore winds are a principal agent of overturning and vigorous vertical mixing in nearshore water of lakes and inner continental shelves. On short (superinertial) timescales of a few hours, onshore winds create surface currents pushing water against the shore which, via the associated pressure gradient force, creates an undercurrent. The resulting overturning circulation rapidly becomes dynamically unstable due to the Kelvin-Helmholt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Note that the classical Ekman layer theory shows that the surface current is deflected 45° to the right with respect to the surface wind direction in the Northern Hemisphere and that coastal upwelling/downwelling could be created by longshore winds (Ekman, 1905). However, the classical Ekman upwelling/downwelling circulation does not reach the shallow waters of the inner continental shelf (Ekman, 1905; Kämpf, 2017; Lentz & Fewings, 2012; Tilburg, 2003), such as the study area in this paper, where the water depth in most regions is approximately 20.0 m (Figure 1b). The water body is so shallow that it is impossible to spatially separate the surface and bottom Ekman layers, and in this situation, wind‐induced currents tend to be aligned with the wind direction (Ekman, 1905; Kämpf, 2015; Lentz & Fewings, 2012).…”
Section: Physical Mechanismsmentioning
confidence: 93%
See 1 more Smart Citation
“…Note that the classical Ekman layer theory shows that the surface current is deflected 45° to the right with respect to the surface wind direction in the Northern Hemisphere and that coastal upwelling/downwelling could be created by longshore winds (Ekman, 1905). However, the classical Ekman upwelling/downwelling circulation does not reach the shallow waters of the inner continental shelf (Ekman, 1905; Kämpf, 2017; Lentz & Fewings, 2012; Tilburg, 2003), such as the study area in this paper, where the water depth in most regions is approximately 20.0 m (Figure 1b). The water body is so shallow that it is impossible to spatially separate the surface and bottom Ekman layers, and in this situation, wind‐induced currents tend to be aligned with the wind direction (Ekman, 1905; Kämpf, 2015; Lentz & Fewings, 2012).…”
Section: Physical Mechanismsmentioning
confidence: 93%
“…ZHAI ET AL. Across-shelf winds are the primary mechanisms for coastal currents in the study area in both winter and summer (Kämpf, 2017;Tilburg, 2003).…”
Section: Zhai Et Almentioning
confidence: 99%
“…Further, the relatively shallower shelf over which the Merrimack plume spreads (∼50 m maximum) is mainly considered a "shallow water region" where interference occurs between the bottom and surface Ekman layers (typically layers are ∼45 m deep at midlatitudes with a 5 m s −1 wind), effectively shutting down Ekman circulation (unlike plumes which discharge over the deeper Pacific shelves e.g.) and aligning plume and ambient shelf surface currents with the instantaneous wind (Kämpf, 2015(Kämpf, , 2017 shown in Figure 3). Therefore, the direct enhancement or diminishment of velocities in the interior plume during wind events in this study (mainly over 4 m s −1 , not shown) was considered a significant control on near-and midfield straining and dissipation of variance and builds on the work of Kakoulaki et al (2014).…”
Section: Tidal Time Scale Wind Transport Effects In the Merrimack And...mentioning
confidence: 99%
“…Winds less than that allow rotation and plume discharge to dominate transport, and the authors speculate larger scale circulation patterns would gain influence in deeper water beyond the midfield plume, or nearshore if winds sustain direction and magnitude at subtidal time scales. Because the Merrimack plume and winds evolve mainly at tidal time scales, the plume is not influenced in a meaningful way by Ekman processes which typically develop under steady wind forcing over multiple days in midlatitude regions (Kämpf, 2017). Further, the relatively shallower shelf over which the Merrimack plume spreads (∼50 m maximum) is mainly considered a "shallow water region" where interference occurs between the bottom and surface Ekman layers (typically layers are ∼45 m deep at midlatitudes with a 5 m s −1 wind), effectively shutting down Ekman circulation (unlike plumes which discharge over the deeper Pacific shelves e.g.)…”
Section: Tidal Time Scale Wind Transport Effects In the Merrimack And...mentioning
confidence: 99%
“…In the study area, winter monsoon winds blew onshore (Figure 1a). In such shallow water in nearshore areas, onshore winds first created shoreward currents in the surface layer, then generated downwelling along the coast, and at last induced seaward currents below the surface layer (Kämpf, 2017).…”
Section: Mechanismsmentioning
confidence: 99%